NAFKAH IDDAH AKIBAT TALAK BA`IN DALAM PERSPEKTIF KEADILAN GENDER (Analisis Terhadap Hukum Perkawinan Indonesia) - Maulida, Fadhilatul; Busyro, Busyro (Alhurriyah, 2018)
Iddah is one of the obligations for a wife who is divorced by her husband, whether divorce is caused by divorce from a husband or because of a wife's lawsuit to the court (khulu '). While undergoing iddah, the wife has the right to obtain housing and living facilities, as is the case in raj'i talak. On the other hand, in the Talak Ba'in, the Islamic marriage law in Indonesia does not provide an opportunity for the wife to earn a living even though she has to undergo the same obligation, namely undergoing iddah and living in her husband's house. This is certainly not in line with gender justice that carries the equality of men and women in this life. Judging from the thoughts of the ulema of the school of thought, actually the legal thinking of Imam Abu Hanifah had first argued to give the wife the right to earn a living in divorce even though the divorce was in the form of divorce. It seems that Imam Abu Hanifah's opinion should be considered in the renewal of Islamic marriage law in Indonesia, especially in realizing justice to the women in their marriage and divorce.